Pembentukan Dajare Pada Drama 99.9 ~Keiji Senmon Bengoshi~ Season Dua Episode Dua - Talin Salisah; Agus Suherman Suryadimulya; Nani Sunarni (KIRYOKU, 2021)
Japanese has a wordplay similar to the English wordplay, puns. The wordplay term is dajare. Dajare is a wordplay that relies on identical words, where the meanings are different. This article focuses on the formation of dajare sentences in the drama 99.9 ~Keiji Senmon Bengoshi~ season two episode two from nine episodes. The analysis process was using qualitative methods. The results of the analysis of the dajare sentences found in the drama show that particles can also help in the formation of dajare. In addition, the speaker or dajare the speakers will look for the exact word that he wants to say. In view of the response of humor itself, depending on the atmosphere and feelings received by the listener.